Mandibular second premolar agenesis: A retrospective cross-sectional study from Palestine - Naji Z Arandi; Tarek Rabi (Wolters Kluwer Medknow Publications, 2024)
Objectives: This retrospective study aimed to determine the prevalence of congenitally missing mandibular second premolars. Materials and Methods: A total of 1,843 radiographs were collected from five different cities in Palestine. Two experienced dentists independently examined the panoramic radiographs and demographic data (age and gender). Results: Among the 1,843 radiographs, 1,039 were for females (57.37%) and 804 were for males (43.63%); 13 cases had at least one congenitally mandibular second premolar. The prevalence of congenitally missing mandibular second premolars in the study population was 0.7%. There was no significant association between gender and mandibular second premolar agenesis. Unilateral agenesis was more common than bilateral, and the left side had more cases of congenitally missing mandibular second premolars than the right side. Conclusions: The prevalence of congenitally missing mandibular second premolars in this study population was 0.7%, within the range reported in other populations.